2021
DOI: 10.7759/cureus.19229
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Citation Rates in High-Impact Glioblastoma Clinical Trials

Abstract: Clinical trials are at the top of research study designs and tend to attract high citation numbers. Glioblastoma multiforme (GBM) is a multidisciplinary disease that continues to be the subject of peak research interest. In general, the literature relating to the predictors of citation rates in clinical trials remains limited. This review aims to identify the factors that influence citation numbers in high-impact GBM clinical trials. The 100 most cited GBM trials of any phase published from 1975 to 2019 were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…11 It is generally accepted that article citation rates correlate well with the publishing journal IF. 1 , 2 , 9 In this study, Neurosciences publications had mean citations of 11.6 and total citations of 2,669.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…11 It is generally accepted that article citation rates correlate well with the publishing journal IF. 1 , 2 , 9 In this study, Neurosciences publications had mean citations of 11.6 and total citations of 2,669.…”
Section: Discussionmentioning
confidence: 69%
“…Similar findings were reported by others. 1 , 3 , 8 , 9 The most frequent study designs were retrospective case series and cross-sectional studies, while the most frequent LOE was IV. A significant correlation between citation numbers and study design, and LOE was observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations